Kampung Arab in Tegal: A Study about Hadrami Society - Siti Rohmah Soekarba; Nur Istiqomah; Ammar Al Haqbani (Indonesian Journal of Arabic Studies, 2025)
Purpose –This study examines the Hadrami community in Tegal within the broader academic discourse of diaspora studies, identity formation, and Arab–Indonesian sociocultural interaction. While Hadrami migration to Indonesia has been widely documented in major cities such as Jakarta, Surabaya, and Pekalongan, very little attention has been given to medium-sized cities like Tegal. This gap is academically relevant because smaller communities reveal how diaspora identity is negotiated in everyday, semi-urban environments rather than in dominant economic hubs. Design/methods/approach –This study examines the Hadrami community in Tegal within the broader academic discourse of diaspora studies, identity formation, and Arab–Indonesian sociocultural interaction. While Hadrami migration to Indonesia has been widely documented in major cities such as Jakarta, Surabaya, and Pekalongan, very little attention has been given to medium-sized cities like Tegal. This gap is academically relevant because smaller communities reveal how diaspora identity is negotiated in everyday, semi-urban environments rather than in dominant economic hubs. Findings –The findings show a dynamic relationship between cultural preservation and integration: religious institutions sustain communal identity, while economic activities strengthen their local presence. Research implications – Theoretically, the study contributes to diaspora and ethnic-identity scholarship by illustrating that Hadrami identity is contextually shaped by localized social structures. Practically, the findings highlight the importance of documenting minority community heritage in regional Indonesia.